GAMBARAN DESKRIPTIF PRILAKU MEMBOLOS SISWA SMP KELAS VII DAN VIII DI SMP KARTIKA XIX-2 - Wulan dari; Ecep Supriatna; Euis Eti Rohaeti (IKIP Siliwangi, 2022)
This study aims to determine the description of student truancy behavior in SMP Kartika XIX-2. This type of research is a descriptive research with a quantitative approach. The population in this study were students of class VII and VIII at SMP Kartika XIX-2 Bandung. The sample in this study amounted to 152 students. The sampling technique in this study is saturated sampling, with the aim that each population is used as a sample. The data collection technique used was in the form of a questionnaire, which consisted of indicators of truancy behavior and factors causing truancy. From the results of the data analysis of truancy behavior there are 33% (50 students) truant behavior is categorized as high, 48% (73 students) are categorized as being truant behavior and only 19% (29 students) are declared low in truancy behavior. Based on the results of research conducted by researchers, it is known that there are 2 factors that cause truancy behavior, namely internal factors from within the child itself and external factors, namely from the surrounding environment, family, friends, and school environment.Keywords: : truancy behavior, truancy factor